Pengaruh Kerapatan Populasi dan Dosis SP-36 Pada Tanaman Kacang Merah Varietas Inerie di Dataran Rendah Terhadap Kualitas Fisiologis dan Kimiawi Benih - Yosefina Lewar; Yohanis H. Dimu Heo; Senny J. Bunga (Politeknik Pertanian Negeri Kupang, 2017)
A good quality seed is obtained from good and appropriate production process. The use of good quality seeds could increase crop production plants, including Inerie variety of red bean. This plant could be grown in the lowlands having modified micro-climate. One simple technology to modify the micro-climate of the plant is through plant population density setting followed by the use of balanced fertilizer, including P fertilizer which could result in high quality seeds. This research was conducted in the Practical Garden of Kupang State Agricultural Polytechnic from April to November 2015. The results of the study showed that 1) the population density affected the levels of seed free fatty acids in the lowest population density of 36 plants / 3 m2 (50 cm x 30 cm); 2) the doses of SP-36 fertilizer affected the germination percentage of the seeds at the highest dose of 200 kg / ha SP-36, and free fatty acid of the seed on lowest level without SP-36 fertilizer , and; 3) there was interaction between the treatment plant and the population density of the dose SP- 36 fertilization. Treatment population density of 36 plants (spacing of 50 cm x 20 cm) with a dose of SP-36 200 kg / ha was the best effect on the rate of growth of seeds, simultaneity sprouted seeds and the content of P-Total on Inerie variety of red beans planted in lowlands eventhough did not have a different result with a spacing of 40 x 20 cm with a dose of SP-36 200 kg / ha. The results of the study served as a model in the development of Inerie variety of red bean in lowlands. Keywords: Production, Quality, Seed, Inerie Red Beans, Lowlands